2018
DOI: 10.1093/jee/toy063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low-Energy Microwaves Technology (Termatrac) for Detecting Western Drywood Termite in a Simulated Drywall System

Abstract: Detecting drywood termites in structures is very challenging. Microwaves technology (Termatrac T3i) is a nondestructive method for detecting drywood termites in structures. Termatrac device and its mobile application provide a bar as well as a line graph when detecting insect movements, but interpreting these graphs is very subjective. In this paper, Termatrac's output signal is quantified using a new method to study the effect of wall layers, wood type, and termite density on signal strength measured as area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
8
1
1
Order By: Relevance
“…Taravati (2018) [26] has reported some limitations with Termatrac that may cause false-negative inspection results (i.e., detection of nontermite objects, movement by the person holding the device, reduced sensitivity with an increasing depth of the building materials, and termite inactivity during an inspection). In this study, in addition to inspection with Termatrac, the treatment zone was also thoroughly visually inspected for drywood termite frass (fecal pellets) and "kick-out holes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taravati (2018) [26] has reported some limitations with Termatrac that may cause false-negative inspection results (i.e., detection of nontermite objects, movement by the person holding the device, reduced sensitivity with an increasing depth of the building materials, and termite inactivity during an inspection). In this study, in addition to inspection with Termatrac, the treatment zone was also thoroughly visually inspected for drywood termite frass (fecal pellets) and "kick-out holes.…”
Section: Resultsmentioning
confidence: 99%
“…Careful observations of fluctuations in the output signal were conducted. All factors that may generate false-positive results on Termatrac were considered following Taravati (2018) [26]. Heat treatments were subsequently conducted only in those parts of the condominium units (e.g., kitchens) with apparent termite activity.…”
Section: Study Site and Protocolsmentioning
confidence: 99%
“…It is a radar based system, which responds to movement [ 12 ]. The maximum reliable wood depth for detecting termites was 5 cm [ 13 ], which is limiting for evaluation of larger wooden structures, such as power poles. Evaluation of the Termatrac ® system revealed that operator skill was critical in establishing its efficacy in termite detection.…”
Section: Introductionmentioning
confidence: 99%
“…(Su and Scheffrahn 1988, Grace et al 1989, Su et al 1993 (Buchli, 1956;Shimizu, 1970;Su, 1991 (Erhorn, 1934;Greaves, 1962;King, 1969 (Su, 1988(Su, , 1993Thorne et al, 1996;Tsunoda et al, 1998Tsunoda et al, , 1999 Sattar et. al., 2007 (Barway et al, 2015;Taravati, 2018 (Fujii, 1975;Su et al, 1983Su et al, , 1988Grace et al, 1989;Grace and Abdallay, 1990;Forschler, 1994;Thorne et al, 1996;Evans, 2000;Atkinson, 2000Atkinson, , 2004aAtkinson, , 2004bNobre et al, 2007 (Su, 1988(Su, , 1993Forschler and Townsend, 1996;Thorne et al, 1996;Tsunoda et al, 1998Tsunoda et al, , 1999Evans et al, 1999;Messenger et al, 2005 (Su, 1988(Su, , 1993Forschler and Townsend, 1996;Thorne et al, 1996;Tsunoda et al, 1998Tsunoda et al, , 1999…”
mentioning
confidence: 99%
“…하지만 측정 당시 해당 장치에 대한 측정 간격 및 방법 등 측정 조건이 결과보고서에 기재되어 있지 않아 기관별 측정 자료 결과에 대한 표준화가 어려울 것으로 판단되어 이에 대한 측정 당시 기준들을 보고서에 명시해야 할 것으로 사료된다. 또한 해당 2세대 모델의 건 재흰개미 탐지 최대 깊이에 관한 기준 연구는 3.5∼5.0 cm 범위로 수행되었으나(Lewis et al, 1998;Taravati, 2018) 상 대적으로 건재흰개미보다 함수율이 높은 목재를 가해하 는 지중 흰개미 가해 환경에 따른 수종별 최대 탐지 깊이 및 범위 연구가 진행되지 않은 실정이다.…”
unclassified